REDUCTION OF BENZO (A) PYRENE IN CHARCOAL GRILLED DUCK MEAT BY MARINATING WITH ANDALIMAN (Zanthoxylum acanthopodium, DC) FRUIT JUICE - Sinaga, K.; Legowo, A. M.; Suprijatna, E.; Pramono, Y. B. (Diponegoro University, 2016)
The effect of andaliman fruit juice marination on the amounts of benzo (a) pyrene in charcoal grilled duck meat were investigated in this research. Completely randomized design was used to determine the effect of 4 treatments of andaliman fruit juice concentration (w/v). Twenty four duck meat samples were devided into 4 treatment groups, those were 0% (I), 10% (II), 20% (III) and 30% (IV). Each group consisted of 6 samples. Total Fat, Tio Barbituric Acid (TBA) value and antioxidant activity were measured from all samples. The result showed there was no effect on total fat of duck meat. Antioxidant activity was 18.60 %, 18.06 %, 19.99 % and 7.54 % for andaliman fruit juice of 10%, 20%, 30% and 0%, respectively. TBA value was 1.03 %, 0.89 %, 0.09 % and 0.10 % for treatment II, III, IV and I, respectively. Antioxidant activity of andaliman fruit was decreased the amounts of Benzo (a) pyrene of duckmeat. Charcoal duck meat without andaliman fruit produced 787 ng, it was higher than charcoal duck meat with andaliman fruit (295 ng).